PENERAPAN METODE LINEAR CONGRUENT METHOD (LCM) PADA PERANGKAT LUNAK TEBAK HURUF HIRAGANA BERBASIS ANDROID - Arief, Rieko Insan; Wahyuni, Linda; Puspita, Khairani (IT (INFORMATIC TECHNIQUE) JOURNAL, 2019)
Japan was industrialized countries about the technology , which is why many of us who want to to japan as the learner and workers , to be able to visit to japan by students and workers in haruskan to speak to japan with passive . Japanese language is any of the languages use of the letter of the alphabet  from which it differs in the writing of international standards .So that japanese difficult learned , because learning not only memorization hurufnya course , but writing and design of hurufnya must also be controlled .This seems to be important to examined deeper , so that made application that may help someone especially for indonesians in studying japanese on a level novice namely hiragana.This is because a student not only needs the book as a medium of learning, but more than that required a more effective and interesting media. Every lesson needs a test or test to measure the distance from what is being learned. This system will be built based on the client server that uses the computer as a web-based server and the Android device as its client. The design of this system is built using Brackets, Notepad ++, XAMPP, Browser. Application design using Linear Congruant Method (LCM) method for randomisation of test.